Biodegradation of Cellulose Containing Gum Product Utilized as Salt Binders and Fuels in the Slurry Explosives by Bacillus thuringiensis (BAB-2592) - A, Anuradha; Paul, Biswajit; J, Jagdish (Asian Journal of Biological and Life Sciences, 2015)
Cellulose based gums (guar gum, xanthan gum, tropica starch, acacia gum, maize starch etc.) are the basic ingredients used for binding and encapsulation of the air/N2 gas bubbles in the slurry explosives. The gumming materials are used in the two or more combinations considering the shelf-life of the finished products. Bacterial isolates from contaminated soil were grown in minimal medium and screened for gums (guar gum and xanthan gum) degradation. The isolates A1 exposed maximum growth selected for detailed studied. Morphological and biochemical analysis, as well as 16 rRNA gene sequence comparison, demonstrated that B. thuringiensis thereof are found prominent culture to decompose the carbon and for breaking of polymeric chain developed during production.
Keywords: Bacillus thuringiensis; Biodegradation; Guar gum; Xanthan gum